NEPHROPROTECTIV EFFECTS OF CANDESARTAN ON DIABETIC NEPHROPATHY IN RATS - Trojacanec, Jasmina; Pavlovska, Kristina; Gjorgjievska, Kalina; Kolovchevski, Nikola; Shikole, Emilija; Labachevski, Bojan; Nikodinovski, Aleksandar; Kikerkov, Igor; Zafirov, Dimche (Journal of Morphological Sciences; Vol 6 No 3 (2023): JMS, 2023)
Diabetic nephropathy (DN) stands out as a primary contributor to end-stage kidney damage. The renin-angiotensin system (RAS) plays a pivotal role in the advancement of DN, making angiotensin receptor blockers (ARBs) particularly noteworthy due to their influence on angiotensin II in DN development. This study investigated the impact of the angiotensin receptor blocker candesartan (CAN) on rats with streptozotocin (STZ)-induced DN, characterized by albuminuria, renal hypertrophy, and mild glomerulosclerosis. DN was induced in normotensive Wistar rats through a single injection of STZ (60 mg/kg ip). STZ administration led to diabetes mellitus (DM) symptoms and DN indicators, such as poor general condition, weight loss, increased kidney weight, elevated serum creatinine levels and BUN, augmented diuresis, and notable albuminuria. These manifestations were prominent at 4 weeks, intensifying further at 8 and 12 weeks post-STZ injection. Commencing candesartan treatment (5 mg/kg BW) at the 4-week mark post-STZ injection significantly alleviated all DN symptoms, reducing serum creatinine values and BUN, albuminuria, and diuresis. Histopathological examination at 8 and 12 weeks revealed that candesartan effectively mitigated glomerulopathy progression, improved the glomerulosclerotic index, and attenuated renal histological abnormalities induced by STZ. In conclusion, candesartan treatment ameliorates STZ-induced nephropathic changes in DM rats.  Key words: Diabetic Nephropathy, streptozotocin, candesartan, Glomerulosclerosis, Rats.